PENGARUH KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE(Studi Pada Pengguna Aplikasi Shopee Di Jakarta Timur) - Venny Herlina (2021)
Shopee is an online marketplace that can easily and quickly make buying and selling online. Shopee offers a wide range of products from fashion to daily necessities. The purpose of this study was to determine and prove whether the Purchase Decision in the Shopee Marketplace has an influence on the variables of Online Consumer Reviews, Prices, and Promotions. This research is a quantitative research. The population taken from the research object is the Shopee Application User. The sample used was 75 respondents with nonprobability sampling method specifically purposive sampling as a sampling technique. Data were collected by using a questionnaire and using a PLS (Partial Least Square) calculator. The results show that: (1) Online Consumer Reviews have a positive and significant effect on Purchase Decisions, (2) Price has no significant effect on Purchase Decisions, (3) Promotion has a positive and significant effect on Purchase Decisions.